Semi Queer : Inside the World of Gay, Trans, and Black Truck Drivers - Balay, Anne (Book collections on Project MUSE., 2018)
Long-haul trucking is linked to almost every industry in America, yet somehow the working-class drivers behind big rigs remain largely hidden from public view. Gritty, inspiring, and often devastating oral histories of gay, transsexual, and minority truck drivers allow award-winning author Anne Balay to shed new light on the harsh realities of truckers' lives behind the wheel. A licensed commercial truck driver herself, Balay discovers that, for people routinely subjected to prejudice, hatred, and violence in their hometowns and in the job market, trucking can provide an opportunity for safety, welcome isolation, and a chance to be themselves - even as the low-wage work is fraught with tightening regulations, constant surveillance, danger, and exploitation.